Design of Employee Attendance Data Information System Using Web- Based QR Code at Medan City Election Commission Office - Idzani Muttaqien Nasution; Ihsan Lubis; Husni Lubis (Indonesian Journal of Education, Social Sciences and Research (IJESSR), 2022)
One of the government organizations tasked with planning general elections honestly in order to carry out elections is the Medan City KPU Office. The issue is that fingerprints are still used in the attendance system used by staff members at the KPU office in Medan. However, the fingerprint machine frequently has issues, for instance, when there is a power outage, employees are unable to use the fingerprint scanner, which can affect attendance. In order to avoid having employees wait in line to check their attendance at work using fingerprints, this study suggests a web-based application to record and arrange all types of attendance data collecting or attendance hours into the information system using a QR Code. In order to avoid having employees wait in line to check their attendance at work using fingerprints, this study suggests a web-based application to record and arrange all types of attendance data collecting or attendance hours into the information system using a QR Code. The PHP programming language and MySQL database are used in stages of the Waterfall approach for system development. Using the QR Code, the author will create a web-based application that will serve as an attendance data information system. It is intended that the application that is created would make it easier and faster to recapture staff attendance, making the process more ideal, efficient, and successful.